IEEE Colombian Conference on Communication and Computing (IEEE COLCOM 2015) 2015
DOI: 10.1109/colcomcon.2015.7152093
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of future AMI applications in Smart Grid Neighborhood Area Networks

Abstract: Smart Grid constitutes the next generation of electricity delivery systems that intend to enhance reliability, efficiency, and security of the power grid. A fundamental component of this intelligent network is the Advanced Metering Infrastructure (AMI), which provides a two-way communication network between Utilities and a collection of smart meters located at the customers side. The interconnected meters form Neighborhood Area Networks that provide a platform for the deployment of customized AMI applications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…SMs send periodic and/or on-demand meter readings to utilities or users for billing and other purposes. The average packet size is around 200 bytes and required transmission data rate is less than 128 kbps [6]. AMR is delay-tolerant and inter-reading time may span between one hour and one month.…”
Section: Automatic Meter Reading (Amr)mentioning
confidence: 99%
See 2 more Smart Citations
“…SMs send periodic and/or on-demand meter readings to utilities or users for billing and other purposes. The average packet size is around 200 bytes and required transmission data rate is less than 128 kbps [6]. AMR is delay-tolerant and inter-reading time may span between one hour and one month.…”
Section: Automatic Meter Reading (Amr)mentioning
confidence: 99%
“…Latency tolerance is 100 ms only, with packet sizes around 210 bytes, and data rates between 10 and 100 kbps [6].…”
Section: Real-time Pricing (Rtp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Each service has different network requirements in terms of network capacity, delay delivery, etc. Previously, it was shown that it was not always feasible to deploy a single type of communications network to cover all the services of the AMI network, and a wireless heterogeneous network (WHN) was expected to be deployed instead [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Power consumers receive also real time power pricing allowing them to have an www.ijacsa.thesai.org active role regarding their consumption patterns. AMI data traffic description provided in Table 1 was elaborated after consulting various research articles surveying smart grid services [10] [11].…”
Section: B Actors Roles and Interactionsmentioning
confidence: 99%